Description of two new species of Claustropyga Hippa, Vilkamaa & Mohrig (Diptera, Sciaridae) from the northern Palaearctic - Vilkamaa, Pekka (Zootaxa, 2024)
Claustropyga alveata sp. n. and C. caetrata sp. n. from the northernmost Palaearctic are described and illustrated. Claustropyga alveata sp. n. has a highly modified tegmen and unusual gonocoxal apodemes, and C. caetrata sp. n. has an uncommonly shaped apical tooth of the gonostylus. The newly described species raise the number of known species of Claustropyga to twenty-seven.